Conserved charges in the quantum simulation of integrable spin chains. (21st April 2023) - Maruyoshi, Kazunobu; Okuda, Takuya; Pedersen, Juan W; Suzuki, Ryo; Yamazaki, Masahito; Yoshida, Yutaka
Abstract: When simulating the time evolution of quantum many-body systems on a digital quantum computer, one faces the challenges of quantum noise and of the Trotter error due to time discretization. For certain spin chains, it is possible to discretize the time evolution preserving integrability, so that an extensive set of conserved charges are exactly conserved after discretization. In this work we implement, on real quantum computers and on classical simulators, the integrable Trotterization of the spin- 1 / 2 Heisenberg XXX spin chain. We study how quantum noise affects the time evolution of several conserved charges, and observe the decay of the expectation values. We in addition study the early time behaviors of time evolution, which can potentially be used to benchmark quantum devices and algorithms in the future. We also provide an efficient method to generate the conserved charges at higher orders.